Content Validation of the Competencies Component of Building Maintenance Management for Waqf-based Religious Schools - Arshad, Huraizah; Mohd Ali, Siti Nadiah; Fauzi, Nurul Sahida; Ihsan, Hidayatul (Environment-Behaviour Proceedings Journal, 2023)
The competency of school administrators in maintaining a school building is paramount in ensuring the safety and comfort of the students and teachers. It also safeguards the functionality of the school facilities towards providing an effective teaching and learning process. Therefore, this research embarked on a quantitative approach to develop and validate building maintenance competency components, focusing on Islamic religious schools using the content validation technique. There are nine components of building maintenance management competencies with forty elements from the literature. Six experts were chosen to evaluate and validate all the items. The result of the study emphasizes the technical and behavioral competencies among the school administrators, which significantly contribute to the effectiveness of Islamic religious schools in Malaysia.